PENGEMBANGAN MEDIA BINGKAI BERGAMBARDENGAN TEMA KONDISI GEOGRAFIS DAN MATA PENCAHARIAN UNTUK PEMBELAJARAN IPS DI MI KELAS IV - Edy Musthofa (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT This study aims to produce picture frame learning media with the theme of geographical conditions and livelihoods activity for social studies learning for 4th grade of elementary School. This study also aims to determine the instructional media decent picture frame for social study learning for 4th grade of elementary School based on media validation by matter expert, media validation by media expert, the test media use by teachers and students. This research iscategorized as Researchand Development(R &D). The studywas conductedwithseveralstages such as, the data collection stage, the planningstage, development stage, as well asthe mediavalidation andtestmedia use. Data collection instrumentsused inthisresearchisthe development ofa questionnaire. Datawere obtainedfromthe results ofthe mediavalidation bya matter expert, the results ofthemedia validationbya mediaexpert, the results of test media use byateacher, andthe results of test media use by fourelementary School studentsof 4th grade. The data obtained wereconvertedinto likertscale todeterminethe category ofpictureframe learning media. It is worthy tobe usedwhen media validation by matter experts, media validationbymediaexperts, testmedia usebyteachersandstudentshas a good mean score ofminimumcategory. The results of the research of "Produce Picture Frame Learning Media with The Theme of Geographical Conditions and Livelihoods Activity for Social Studies Learning for 4th Grade", considered worthy to use in social studies learning. It can be seen from the results of the media validation by matter experts who have an average final score of 4.3; results of the validation media by media experts have an average final score of 3.7; test media use by teacher had a mean score of 4.85; test media use by students has the lowest mean score of 3.7 and the highest mean score of 4.85 and had class mean score of 4.51. From the results it appears that the average instructional picture frame media is worthy to be used for social studies learning with good quality. Keywords:pictureframe learning media,social studies learning.